Thought stopping: public speaking anxiety - Fajriani, Indah; Diani, Rahma; Anggun, Tarisa (KONSELI: Jurnal Bimbingan dan Konseling (E-Journal), 2023)
The problem of anxiety when speaking in public is still common today. This problem occurs due to the individual's inability to be with other individuals in public. To overcome this problem, one thing that can be done is to use the thought stopping counseling technique. The aim of this research was to determine the effect of the thought stopping technique in reducing public speaking anxiety among students at SMPN 1 Abung Surakarta. This research uses a quantitative research approach with experimental research type. The design used is one group pretest-posttest design. The results in this study indicate that the thought stopping technique is effective in reducing public speaking anxiety. The research results showed that public speaking anxiety was reduced after providing group counseling services using the thought stopping technique. The latest thing from this research from previous researchers is the use of the thought stopping technique, which is a technique used to cure negative thoughts that can damage oneself.